?STUDIES ON BIODEGRADABLE ORGANIC FERTILIZING POTS AND CROP ESTABLISHMENT - ASKARI, ABID; ANWAR, NAIIEED; JEHAN, A.; AHMED, S.I. (Biological Sciences - PJSIR, 1995)
Uniform and healthy growth in seedlings is a critical step. Mortalities and growth set-back due to transplanta- tion failure is a common phenomenon. Availability of farmyard manure and agro-wastes in abundance has been taken into consideration for making different categories of biodegradable organic pots. Pots trials were conducted to determine the effect of different ratios of farmyard manure and agrowastes on the growth of plants. A histogram has also been provided to show the comparative growth of plants after six months set and biodegradation in the soil. The best result was achieved in 40% farmyard manure pots as compared to 35 and 30% farmyard manure pots. These pots yielded the greatest number of seedlings. The C/N ratio in 40% composition was round favourable as it repre- sented the balanced pH and organic matter. In control set the growth or plants was stunted. under nourished and chlorotic.